Indonesian Commercial Diplomacy to Japan through the Indonesian Trade Promotion Center (ITPC) in the Development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia - Diah Apriliani; Taufik Hidayat; Akim Akim (International Journal of Nusantara Islam, 2022)
Indonesia and Japan have a natural relationship (natural partner) where diplomatic relations have been going on since 1958, and Japan is one of Indonesia's trading partners and investors. The Indonesian government through the Director General of National Export Development of the Ministry of Trade opened a Trade Promotion office, namely the Indonesian Trade Promotion Center (ITPC) Osaka. The purpose of this study is to find out how to implement Indonesian commercial diplomacy towards Japan through the Indonesian Trade Promotion Center Osaka in increasing the export value of MSMEs in Indonesia. This study uses a descriptive qualitative approach with a literature study as a data collection technique. The analysis of this paper will use the theory of commercial diplomacy. This theory is quite comprehensive in explaining various commercial diplomacy activities which include trade, investment, business advocacy and tourism promotion activities. Through the process of data analysis and interpretation, the results of this study are that Indonesian Commercial Diplomacy through ITPC Osaka in increasing the Export Value of Indonesian MSMEs has increased the export value in the last 3 (three) years starting from 2019, but it is still not optimal, because there are several factors including the existence of trade promotions that are still limited to exporters and the requirements for export eligibility in Japan are quite difficult.